Strategies to Enhance Mesenchymal Stem Cell-Based Therapies for Acute Respiratory Distress Syndrome - Jibin Han; Yanmin Li; Yuanyuan Li (Stem Cells International)
Acute respiratory distress syndrome (ARDS) is a multifaced disease characterized by the acute onset of hypoxemia, worsened pulmonary compliance, and noncardiogenic pulmonary edema. Despite over five decades of research, specific treatments for established ARDS are still lacking. MSC-based therapies have the advantage of targeting nearly all pathophysiological components of ARDS by means of a variety of secreted trophic factors, exerting anti-inflammatory, antioxidative, immunomodulatory, antiapoptotic, and proangiogenic effects, resulting in significant structural and functional recovery following ARDS in various preclinical models. However, the therapeutic efficacy of transplanted MSCs is limited by their poor engraftment and low survival rate in the injured tissues, major barriers to clinical translation. Accordingly, several strategies have been explored to improve MSC retention in the lung and enhance the innate properties of MSCs in preclinical models of ARDS. To provide a comprehensive and updated view, we summarize a large body of experimental evidence for a variety of strategies directed towards strengthening the therapeutic potential of MSCs in ARDS.